To what extent could eliminating racial discrimination reduce inequities in mental health and sleep problems among Aboriginal and Torres Strait Islander children? A causal mediation studyResearch in context - Naomi Priest; Shuaijun Guo; Rushani Wijesuriya; Catherine Chamberlain; Rosemary Smith; Sharon Davis; Janine Mohamed; Margarita Moreno-Betancur (Elsevier, 2024)
Summary: Background: Racism is a fundamental cause of health inequities for Aboriginal and Torres Strait Islander children. We estimated the potential reduction in inequities in Aboriginal and Torres Strait Islander children's mental health and sleep problems if interpersonal racial discrimination was eliminated. Methods: We drew on cross-sectional data from the Speak Out Against Racism (SOAR; N = 2818) and longitudinal data from the Longitudinal Study of Australian Children (LSAC; N = 8627). The SOAR was completed in 2017 and the LSAC followed children from 2004 to 2014 in the kindergarten cohort and from 2008 to 2018 in the birth cohort. Exposure: Aboriginal and Torres Strait Islander status (Aboriginal and Torres Strait Islander/Anglo-European), a proxy measure of structural racism (SOAR: 10-15 years; LSAC: 4-5 years); Mediator: interpersonal racial discrimination (yes/no) (SOAR: 10-15 years; LSAC: 12-13 years); Outcomes: mental health problems (yes/no) and sleep problems (yes/no) (SOAR: 10-15 years; LSAC: 14-15 years). An interventional effects causal mediation approach was used. Findings: Aboriginal and Torres Strait Islander children had higher prevalence of mental health problems (SOAR: 40.1% versus 13.5%; LSAC: 25.3% versus 7.6%) and sleep problems (SOAR: 28.5% versus 18.4%; LSAC: 14.0% versus 9.9%) than Anglo-European children. Hypothetical interventions eliminating Aboriginal and Torres Strait Islander children's experiences of interpersonal racial discrimination could reduce 42.4% and 48.5% of mental health and sleep inequities in SOAR (equivalent to 11.2% and 4.7% absolute reductions) and 25.6% and 1.6% of mental health and sleep inequities in LSAC (equivalent to 5.5% and 0.1% absolute reductions). Absolute remaining inequities were similar across both studies for both outcomes. Interpretation: Targeted policy interventions that eliminate racial discrimination against Aboriginal and Torres Strait Islander children could have high potential to reduce inequities in mental health and sleep problems. Addressing racism and racial discrimination needs a multi-component and multi-level approach directed by Aboriginal and Torres Strait Islander communities. Funding: National Health and Medical Research Council of Australia and Medical Research Future Fund of Australia.